2017
DOI: 10.1371/journal.pone.0187120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decades of physical driving on body movement and motion sickness during virtual driving

Abstract: We investigated relations between experience driving physical automobiles and motion sickness during the driving of virtual automobiles. Middle-aged individuals drove a virtual automobile in a driving video game. Drivers were individuals who had possessed a driver’s license for approximately 30 years, and who drove regularly, while non-drivers were individuals who had never held a driver’s license, or who had not driven for more than 15 years. During virtual driving, we monitored movement of the head and torso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…However, Chang et al (2017) did not find any differences in incidence and severity of simulator sickness between drivers and non-drivers of the same age-group. In a similar study, Stoffregen et al (2017) reported that although drivers developed simulator sickness quicker than non-drivers compared to non-drivers, severity of the symptoms was not affected by experience. Another explanation could be based on the postural sway theory.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, Chang et al (2017) did not find any differences in incidence and severity of simulator sickness between drivers and non-drivers of the same age-group. In a similar study, Stoffregen et al (2017) reported that although drivers developed simulator sickness quicker than non-drivers compared to non-drivers, severity of the symptoms was not affected by experience. Another explanation could be based on the postural sway theory.…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, simulator sickness occurs when a person attempts to maintain stability in a new environment in which the body has not yet learned strategies to preserve postural stability (Riccio and Stoffregen 1991). Research on the postural instability theory revealed that postural instability can predict both motion and simulator sickness (Stoffregen and Smart 1998;Smart, Stoffregen, and Bardy 2002;Stoffregen et al 2000;Stoffregen et al 2017). A further study in which the position of participants was fixated reported relief in simulator sickness symptoms in older participants and thus supports the postural instability theory (Keshavarz et al 2017).…”
Section: Possible Explanations For Simulator Sicknessmentioning
confidence: 79%
“…Other studies suggested the influence of age, with older adults being generally more susceptible to SS [ 2 , 26 , 29 , 33 , 36 ]. Some researchers found a link between SS and specific movement patterns or postural instability, the latter of which was reported to be more prevalent in older adults and females [ 24 , 33 , 40 , 47 , 70 , 71 ]. Additional participant-related factors reportedly increasing susceptibility include lower concentration level, variable mood and energetic arousal, weaker feeling of presence in simulated environment, tendency for pain catastrophising, higher anxiety levels, neuroticism, perceptual style, Chinese ethnicity, health status, and even better aerobic fitness [ 15 , 37 , 38 , 39 , 40 , 41 , 61 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, relatively few studies have explored such participant-related factors as participants’ experiences. When they have, they usually focused on the effect of either repeated participation in simulations [ 26 , 42 , 43 , 44 , 45 ] or length of real-life driving experience [ 41 , 46 , 47 ]. In addition, current research on driving-related SS/MS/CS tends to use fixed-base simulations [ 24 , 32 , 34 , 46 , 47 ], which offer fewer motion cues than real-motion ones.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies report postural precursors of motion sickness in movement magnitude preceding the onset of motion sickness symptoms in physical environments [38], video games [39], and virtual reality headsets [27]. Additionally, other measures of movement that are orthogonal to magnitude have also been implicated in motion sickness such as the width of the multifractal spectrum [27] and temporal movement dynamics [40]. While the literature on the relationship between postural instability and motion sickness is extensive, there is some debate on the exact nature of the relationship.…”
Section: Discussionmentioning
confidence: 99%